Numerical inverse analysis applied to the determination of the adiabatic temperature rise curve in concrete - Zappitelli, María Paula (2024)
Thermal shrinkage is one of the principal causes of cracking in massive concrete structures. If concrete volume changes are restricted and thermal stresses exceeds concrete tensile strength, cracking occurs. For the purpose of calculating thermal stresses, it is necessary to perform a heat transfer analysis to determine the temperature evolution in concrete structures. One of the main parameters in this analysis is the adiabatic temperature rise curve. The determination of this curve can be performed through adiabatic or semi-adiabatic calorimeters or analytical expression. But the former alternative is complicated to implement on the construction site, and the latter is difficult to implement for new cement formulation such as blended cements. An alternative is to perform the inverse analysis using the temperature readings recorded by thermocouples. In this paper an inverse analysis combined with a FEM model is proposed to determine the adiabatic temperature rise curve in a concrete cube, in order to use it to predict temperature evolution in a concrete slab made with the same concrete.